A constructability assessment method (CAM) for sustainable division of land parcels. (November 2016) - Brennan, Thomas M.; Venigalla, Mohan
Abstract: Historically the land development process has lacked a decision support structure for evaluating undeveloped parcels of land for compatibility with land use policy and engineering constraints. This paper demonstrates an applied multi-criteria decision support structure for characterizing the spatial distribution and classification of a parcel's potential to support residential lot construction. This support structure is based on parcel attributes quantified in a typical site feasibility report, to include: potential house yield, wetlands area, soil types, streams (surface drains), and steep slope areas. The analytical capabilities of geographic information system (GIS) are employed in the decision support structure named the constructability assessment method (CAM). CAM integrates a dynamic multi-criteria attribute assessment method, based on the Analytical Hierarchy Process (AHP), for a given set of administrative requirements, and engineering constraints and judgment. The results of a case study using CAM characterized the approximate location of ideal lots for homes construction in an R-1 zoning district located on a 1290 acre land parcel in Loudoun County, VA, while avoiding existing hydric soils, floodplains, steep slopes, and forested areas. The number of ideal lots for a given set of engineering and administrative constraints represented a 65% reduction from the maximum lots permitted by regulatory constraints alone. The methodology used in this case study provides a consistent and repeatable land parcel analysis technique for undeveloped land parcels, and can be adapted and/or extended to a number of similar publicly available geographic datasets and constraint. In estimating optimal development density, CAM meets the needs of zoning administrators as well as the developers, thus offering a demand-driven market-based solution for sustainable land development.